Mortality among children aged 28 days–17 years with pneumonia who are not severely undernourished and the effect of macronutrient supplementation: a systematic review and meta-analysis - Kathryn Maitland; André Briend; Charles Karamagi; Nakalembe Loyce; Alison Annet Kinengyere; Moses Ocan; Victor Musiime; Andrew Kiggwe; Damalie Nalwanga; Abel Abera Negash (BMJ Open)
Objective Pneumonia is associated with four times higher odds of death among children with severe undernutrition. However, there is an equipoise for the mortality of children without severe undernutrition and the impact of macronutrient interventions. We collated evidence on mortality, anthropometric outcomes and the effect of macronutrient interventions in the management of non-severely undernourished children (28 days–17 years) with pneumonia globally.Design Systematic review and meta-analysis using a priori criteria developed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guideline.Data sources PubMed, Medline, EMBASE, Web of Science, Google Scholar, Scopus, Cochrane Central and bibliographies were searched between January 2000 and July 2024.Eligibility criteria We included articles conducted among children between 28 days and 17 years with pneumonia and non-severe malnutrition that reported on mortality and changes in anthropometric status or macronutrient supplementation. Studies conducted exclusively among adults, on micronutrient supplementation, case studies, commentaries and reviews were excluded.Data extraction and synthesis Two reviewers independently screened, abstracted the data and conducted risk of bias (RoB) using standard criteria including the RoB in non-randomised follow-up studies of exposure for observational studies and the revised Cochrane RoB assessment tool for randomised studies (RoB 2.0). Heterogeneity was assessed using the I2 statistic, and subgroup analysis was done. Data were analysed using both narrative and quantitative synthesis. Quantitative synthesis was done using the maximum likelihood random-effects model in STATA V.18.0, with the ‘meta_es’ command.Results A total of 15 articles were included (11 conducted in sub-Saharan Africa and four in Asia), with 169 901 participants overall. The mortality among non-severely undernourished children with pneumonia was 3.0% (95% CI 2% to 5%, I2=99.38%), with a range of 1–13% across studies. Children with moderate undernutrition had a higher overall mortality, 9.0% (95% CI 6% to 13%, I2=89.50%), than well-nourished children, with a range of 3–19% across studies. Only one of the 15 studies reported anthropometric outcomes during follow-up and compared mortality rates of those who did versus did not receive macronutrients. The study results were inconclusive.Conclusions Mortality among non-severely undernourished children with pneumonia ranges between 1–13% globally. There is inadequate follow-up nutritional assessment and management for non-severely undernourished children with pneumonia.PROSPERO registration number CRD42021257272.